Association Between Age and Ethnicity with Pediatric Clinical Outcomes in COVID-2019 - Jessica Snowden MD, MS; Anjali Patwardhan MD, MRCPCH, MRCPI, MSc, MBA (SAGE Publishing, 2021)
The novel coronavirus SARS-CoV-2 (COVID-19) has infected people across the world, including an increasing number of children in the United States (U.S.). The epidemiology of pediatric infection in the U.S. and how it influences clinical outcomes is still being characterized. In this study, we describe a cohort of 989 children with laboratory-confirmed SARS-CoV-2 infection. Children under age 20 in a statewide health system with SARS-CoV-2 infection, defined by positive PCR testing, between February 1 and August 30, 2020 were included in this observational cohort study. Data extracted from the medical record included age, demographic information, clinical illness severity, hospital stay, and comorbidities. Analysis included descriptive statistics and Chi-square as appropriate. Nine hundred and eighty-children met inclusion criteria for this study, ranging from 1 month to 20 years in age. Most children (62.4%) were asymptomatic at the time of diagnosis and children over the age of 2 were significantly more likely to be asymptomatic at diagnosis than younger children ( P  < .05). Hispanic children were significantly more likely to be symptomatic at the time of diagnosis (56.3% asymptomatic; P  < .05). The high proportion of children with asymptomatic infection emphasizes the importance of understanding the unique role of children in the pandemic. Older children are more likely to be asymptomatic, but also more likely to experience severe or critical illness when symptoms do develop. Hispanic children were more likely to be symptomatic at diagnosis, highlighting the importance of culturally specific outreach to vulnerable communities.